Hiring and retaining skilled employees in SMEs: Problems in human resource practices and links with organizational success - Yuriy Bilan; Halyna Mishchuk; Iryna Roshchyk; Olena Joshi (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
The ability to attract and retain the talents is an important factor in the competitiveness of countries, as it is confirmed in our study. At the level of small and medium-sized enterprises, hiring and retaining skilled workers is one of the most difficult tasks of HR management, especially in transition economies with a high intensity of 'leaching out' the skilled workers due to labour migration. Our research in Ukraine, which is a prime example of such countries, conducted via the cluster analysis allows us to conclude that the problems of hiring and retaining skilled workers have some connection with profitability: there is almost always a problem with filling vacancies with people of all educational levels in unprofitable enterprises, which is not typical of profitable businesses. The main problems with filling vacancies according to employers' estimations are: 1) market factors - shortage of employees with the required skills; 2) internal problems of ensuring the attractiveness of jobs (material - pay, and intangible - career prospects, flexible working hours, legal employment); 3) internal factors of inefficient HR management, including recruiting; 4) psycho-physiological factors of job satisfaction. However, there are no close links between the factors of hiring effectiveness and retention of skilled workers with the economic success of the organization in the form of the growth of assets, revenues and stuff. This leads to the conclusion that the practices of human resources management in small and medium-sized businesses in Ukraine are largely built chaotic, without analyzing the impact on the efficiency of the use of other resources and without providing links with the overall economic efficiency of enterprises.
Keywords: J23; J63; M51; 650; human resource; organizational economic success; SMEs; hiring; retention; vacancies